ANALISIS PERSONAL FINANCIAL LITERACY DAN FINANCIAL BEHAVIOR MAHASISWA STRATA I FAKULTAS EKONOMI UNIVERSITAS SUMATERA UTARA - Darman Nababan; isfenti sadalia (Universitas Sumatera Utara, 2013)
Abstract This study aims to examined personal financial literacy and financial behavior; financial literacy based on the personal characteristics of students, and impact of the financial literacy on financial behavior of undergraduate students of Faculty of Economics, University of Sumatera Utara class rank 2008 through 2011 who still active by June 2011. Financial literacy was measured using 27 multiple-choice questions and a score calculated based on the percentage of the correct answers. Financial literacy and then analyzed based on the characteristics of the respondents consisting of gender, majors, class rank, GPA, and residence (living with parents or living alone / boarding), the level of parental education, and parental income. Financial literacy is also grouped into relatively high and relatively low based on the median to analyze the financial behavior of respondents in each group. The analitical method used is a descriptive statistical analysis. The data used are the primary data obtained from a survey of 97 respondents. The finding indicates that those who are male students, Economic Development major, student of 2008 and 2009, GPA ≥ 3.00, and student who live alone at boarding house, has a higher financial literacy. Meanwhile, female students, Management majors, lower class rank, GPA <3.00, and live at home with parents have lower financial literacy. Overall mean of correct answer of the survey is about 56.61%, so it can be concluded that the respondents had low levels of financial literacy, in addition, the tendency of respondents practicing expected financial behavior did not increase as expected consistently along with the increase of financial literacy. Keywords: Personal Financial Literacy, Financial Behavior, College Student